Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2958.1998.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

nodD2 of Rhizobium sp. NGR234 is involved in the repression of the nodABC operon

Abstract: SummaryTranscriptional regulators of the lysR family largely control the expression of bacterial symbiotic genes. Rhizobium sp. NGR234 contains at least four members of this family: two resemble nodD, while two others are more closely related to syrM. Part of the extremely broad host range of NGR234 can be attributed to nodD1, although the second gene shares a high degree of DNA sequence homology with nodD2 of R. fredii USDA191. A nodD2 mutant of NGR234 was constructed by insertional mutagenesis. This mutant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 47 publications
3
48
0
2
Order By: Relevance
“…B. japonicum nolA and R. meliloti nolR mutants retain the ability to nodulate their respective hosts, albeit at lower efficiency, suggesting that fine-tuning of nod gene expression is required for optimal nodulation. Similarly, a nodD2 mutant of strain NGR234 fails to repress the expression of the nodABCIJnolOnoeI operon after initial flavonoid induction and, in contrast to the wildtype strain, is unable to form nitrogen-fixing nodules on V. unguiculata and Cajanus cajan (73).…”
Section: Mesorhizobium Lotimentioning
confidence: 99%
“…B. japonicum nolA and R. meliloti nolR mutants retain the ability to nodulate their respective hosts, albeit at lower efficiency, suggesting that fine-tuning of nod gene expression is required for optimal nodulation. Similarly, a nodD2 mutant of strain NGR234 fails to repress the expression of the nodABCIJnolOnoeI operon after initial flavonoid induction and, in contrast to the wildtype strain, is unable to form nitrogen-fixing nodules on V. unguiculata and Cajanus cajan (73).…”
Section: Mesorhizobium Lotimentioning
confidence: 99%
“…Knight et al (37) demonstrated that the strong, constitutive expression of the nodulation genes results in defective and reduced nodulation phenotypes on host plants. It is not surprising, therefore, that in addition to positive activation the nod genes are also subject to negative regulation (10,15,21,39). In S. meliloti repression is mediated by NolR, while in Rhizobium sp.…”
Section: Nodd and Beyondmentioning
confidence: 99%
“…strain NGR234 and B. elkani NodD2 acts as a repressor. Mutations to these repressors result in aberrant and delayed nodulation phenotypes (15,39). In B. japonicum, NolA and NodD2 form two key components in the negative regulation of the nodulation genes.…”
Section: Nodd and Beyondmentioning
confidence: 99%
“…Various mutants of Rhizobium sp. strain NGR234 were constructed either by inserting an antibiotic resistance omega cassette into specific genes (giving NGR⍀target gene strains) or by deleting a restriction fragment internal to the target gene and replacing it with an omega antibiotic resistance cassette (resulting in NGR⌬target gene strains) using standard techniques (12). Promoter constructs cloned into the broad-host-range reporter vector pMP220 (52) were mobilized into NGR234 and its derivatives by triparental matings using pRK2013 as the helper plasmid (16).…”
Section: Methodsmentioning
confidence: 99%